Patterns of mitochondrial DNA damage in blood and brain tissues of a transgenic mouse model of Machado-Joseph disease - Kazachkova, Nadiya (2013)
BACKGROUND: Machado-Joseph disease (MJD) is an autosomal dominant spinocerebellar ataxia caused by a CAG tract expansions in the ATXN3 gene. Patterns of mitochondrial damage associated with pathological findings of brain tissues could provide molecular biomarkers of this disorder. OBJECTIVE: The potential of mitochondrial DNA (mtDNA) damage as a biomarker of MJD progression was investigated using a transgenic mouse model. METHODS: DNA was obtained from affected (pontine nuclei) and nonaffected tissues (hippocampus and blood) of transgenic animals of three distinct age groups: 8 weeks, before onset of the phenotype; 16 weeks, at onset, and 24 weeks, at well-established phenotype. Wild-type littermate mice, serving as controls, were analyzed for the same tissues and age groups. mtDNA damage was studied by fluorescence-based quantitative PCR in 84 transgenic and 93 wild-type samples. RESULTS: A clear pattern of decrease in mtDNA copy number with age and accumulation of 3,867-bp deletions at the initial stages (both being more pronounced in transgenic mice) was observed. Pontine nuclei, the affected tissue in transgenic mice, displayed 1.5 times less copies of mtDNA than nonaffected brain tissue hippocampus (odds ratio = 1.21). Pontine nuclei displayed the highest percentage of mtDNA deletions (6.05% more in transgenic mice). CONCLUSION: These results suggest that mtDNA damage is related to the initiation of the phenotype in transgenic mice; mtDNA 3,867-bp deletions may be a biomarker of the initial stages of the disease.